TECHNICAL AND ECONOMIC EFFICIENCY ANALYSES OF THE PRODUCTIVE PERFORMANCE AND EGG QUALITY PARAMETERS IN LAYING HENS FED BY DIETS CONTAINING RAW AND TREATED COMMON VETCH SEED AT DIFFERENT LEVELS - Y. Topcu``; M. Macit; H. Kaya; A. Kaya (Journal of Animal and Plant Sciences, 2014)
The aim of the study was to determine the technical and economic optimum levels of raw and treated common vetch seed (CVS) on the productive performance and egg quality traits in laying hens. One hundred and sixty-eight White (Lohmann) layers, 30 weeks of age were randomly assigned to seven groups, each with six replicate cages of four hens. Control diet (C) and basal diets supplemented with 12.5 and 25% raw CVS (%12.5 Raw Common Vetch Seed: RCVSI and %25 Raw Common Vetch Seed: RCVSII), 12.5% and 25% soaking CVS (%12.5 Soaking Common Vetch Seed: SCVSI and %25 Soaking Common Vetch Seed: SCVSII) and 12.5% and 25% autoclaving CVS (%12.5 Autoclaving Common Vetch Seed: ACVSI and %25 Autoclaving Common Vetch Seed: ACVSII) were offered for 18 wks. Production elasticity (Ep) and the equation of marginal value of physical product (MVPP) and marginal resources cost (MRC) were used to determine technical and economic production levels, respectively. The most effective technical and economic optimum with 60.17 and 63.54 g EW (egg weight) in laying henswere obtained from 117.29 and 106.68 g SCVSI feed intakes, respectively. On the other hand, the highest technical optimum levels were obtained by 2.51 kg cm-2 SS (shell strength) and 89.56 HU (Haugh unit) per 90.91 g ACVSII and 103.97 g RCVSII feed intakes, respectively. The growers could reach to the highest technical and economic optimum levels in laying hens by preferring dietary CVS supplementation vs. C, and thus could provide a major benefit with the effective usage of the scarce source.
Keywords: laying hens; common vetch seed; technical and economic efficiency; performance; egg quality